Wave dynamics and composite mechanics for microstructured materials and metamaterials - Sumbatyan, Mezhlum A. (Springer, 2017)
This volume deals with topical problems concerning technology and design in construction of modern metamaterials. The authors construct the models of mechanical, electromechanical and acoustical behavior of the metamaterials, which are founded upon mechanisms existing on micro-level in interaction of elementary structures of the material. The empiric observations on the phenomenological level are used to test the created models. The book provides solutions, based on fundamental methods and models using the theory of wave propagation, nonlinear theories and composite mechanics for media with micro- and nanostructure. They include the models containing arrays of cracks, defects, with presence of micro- and nanosize piezoelectric elements and coupled physical-mechanical fields of different nature. The investigations show that the analytical, numerical and experimental methods permit evaluation of the qualitative and quantitative properties of the materials of this sort, with diagnosis of their effective characteristics, frequency intervals of effective energetic cutting and passing, as well as effective regimes of damage evaluation by the acoustic methods.
Keywords: Composite materials -- Mechanical properties.; Microstructure.; elektronické knihy; electronic books